Work-related stress in Zimbabwe: an investigation into the nature and understanding of the psychosocial work environment in the financial services sector - Ndengu, Tarisayi (2020)
Most people value work because of the material and psychological benefits that it offers. However, the workplace has become a source of both joy and in some situations sorrow in terms of ill health and in some cases fatalities. Nevertheless, the workplace is also a key place for safeguarding employees’ health through effective work organisation, management and design.